The Role of Environmental Accounting in Improving Company Sustainability: (Empirical Study of Mining Companies in Indonesia) - Murniati, Sitti (Journal of Management, 2024)
The purpose of this study is to investigate the impact of environmental accounting in promoting corporate sustainability, with a focus on Indonesian mining businesses. Environmental accounting is measured using three key indicators: environmental reporting, environmental costing, and environmental investment. Corporate sustainability is evaluated based on environmental, social, and economic performance. The study approach employed was multiple linear regression analysis, employing a sample of ten mining companies listed on the Indonesia Stock Exchange. The findings demonstrated that environmental accounting methods have a favorable and considerable impact on corporate sustainability. Furthermore, business size was discovered to be a moderating element, strengthening the link between environmental accounting and corporate sustainability. This study confirms the need of incorporating environmental accounting into business planning in order to accomplish long-term sustainability objectives. The findings have practical implications for corporate management in terms of enhancing sustainability performance through increased environmental investment and reporting. Future study recommendations include increasing the sample size and testing similar links in other industry areas.